Psychological Process, Social and Environmental Influence on Retirement Planning: Malaysian Energy Industry Perspective - Jais J.B.; Asokumar A. (Sciendo, 2023)
Malaysia currently begins to follow the global trends of an ageing population and expected to be an aged nation by 2040. Due to the unprecedented demographic patterns, ageing population coupled with longer longevity has posed a challenge, as most of the working individuals are still unprepared and not ready to face retirement because of poor planning for their golden years. Similarly, there is a growing aging workforce in the Malaysian energy industry that begets attention for retirement planning. Lack of adequate planning can be an obstacle to achieve a desired retirement life. Therefore, this study examined the determinants (i.e. psychological process, social influence and environmental influence) of employees' retirement planning in the Malaysian energy industry. This study used a life-course, ecological theory to illustrate the relations between the constructs and retirement planning. This study relied on quantitative approach. A total of 171 questionnaires were collected from employees of the energy industry and were analysed using Partial Least Square Structural Equation Modelling (PLS-SEM) to test the proposed hypotheses. The results indicated that the psychological process, social influence and environmental influence have a positive association towards employees' retirement planning in Malaysian energy industry. This study will also highlight some suggestions for improvement to encourage the employees to start saving early to achieve a sustainable quality retired life. 2020 Juraifa Bte Jais et al., published by Sciendo 2020.